Legacy of a 10‐year multidomain lifestyle intervention on the cognitive trajectories of overweight and obese individuals with type 2 diabetes mellitus: Epidemiology / Risk and protective factors in MCI and dementia. (7th December 2020) - Hayden, Kathleen M.; Luchsinger, Jose; Carmichael, Owen T.; Dutton, Gareth; Johnson, Karen C; Kahn, Steven; Rapp, Stephen R.; Yasar, Sevil; Neiberg, Rebecca H.; Espeland, Mark A.
Abstract: Background: Look AHEAD MIND was designed to examine whether a randomized clinical trial designed to induce and sustain long‐term weight losses led to cognitive benefit and to determine the role that baseline weight or history of cardiovascular disease (CVD) played in modifying this association. Method: Participants (N=3, 826; 45‐76 years) were randomized to an intensive lifestyle intervention (ILI) or to diabetes support and education (DSE). We derived a cognitive composite score based on standardized scores on the Look AHEAD battery of tests, including: Digit Symbol Substitution Test (DSST), Rey Auditory Verbal Learning Test, Modified Mini‐Mental State Exam, Trail Making Test (TMT) Parts A&B, and Stroop Color‐Word Test. Mixed effects models were used to determine whether random assignment to ten years of ILI or DSE would leave a legacy of different trajectories of cognitive function over 6‐8 subsequent years. Subgroups identified in our prior work as having potentially different intervention effects including those with BMI >=30 at randomization, and those who had a history of CVD at baseline randomization were studied. Result: There were no significant differences in cognitive composite scores over time by intervention arm. However, there was a significant difference in performance on the TMT‐A (p<0.05), with individuals randomized to ILI performing better than the DSE group at the first two cognitive assessments. These relationships did not differ by baseline BMI. Analyses to examine interactions between baseline CVD status and intervention arm suggested those with baseline history of CVD randomized to ILI performed worse than the DSE group on the DSST (p=0.023) and the Stroop Test (p=0.003) over time. This trend for worse performance among ILI participants with CVD history was seen across all tests but only significant for the DSST and Stroop. Conclusion: There were no significant differences in long‐term cognitive performance by randomization arm with the exception of TMT‐A. Interactions by baseline CVD history on two tests of executive function were found, although all tests showed similar yet non‐significant results. Participants with a history of CVD at baseline do not appear to have received cognitive benefits from the ILI intervention.